2021
DOI: 10.3390/plants10050938
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid’s Role in the Modulation of Compounds that Contribute to Wine Quality

Abstract: Abscisic acid (ABA) plays a crucial role in the plant responses to environmental signals, in particular by triggering secondary metabolism. High-altitude vineyards in Mendoza, Argentina, are exposed to elevated solar ultraviolet-B (UV-B) levels and moderate water deficits (WD), thus producing grapevine berries with high enological quality for red winemaking. Volatile organic compounds (VOCs) and phenolic compounds (PCs) accumulate in the berry skins, possess antioxidant activity, and are important attributes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…Phenolic compounds were the major category identified with positive-ionization LC-HRMS/MS ( Figure 3 ). Increases in trans-resveratrol and piceid were reported in ABA-treated Malbec cultivars [ 21 ], which is consistent with the untargeted LC-MS/MS results in the 2019 wines ( Figure 5 ) from our study. The untargeted LC-MS/MS analysis of wines in this study did not show the consistent effects of exogenous ABA on GRBV-positive Pinot noir.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Phenolic compounds were the major category identified with positive-ionization LC-HRMS/MS ( Figure 3 ). Increases in trans-resveratrol and piceid were reported in ABA-treated Malbec cultivars [ 21 ], which is consistent with the untargeted LC-MS/MS results in the 2019 wines ( Figure 5 ) from our study. The untargeted LC-MS/MS analysis of wines in this study did not show the consistent effects of exogenous ABA on GRBV-positive Pinot noir.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that ABA can have a positive effect on grape phenolic compounds by increasing the total anthocyanin and total phenolic content in grape berry skin at harvest [ 20 ]. ABA may increase low-molecular-weight polyphenols and anthocyanins in final wines [ 21 ]. It has been demonstrated that exogenous ABA can modulate transcription factors involved in the phenylpropanoid pathway differently to increase the amount of petunidin- and malvidin- type anthocyanins, which improve the skin color of grapes [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The spraying of IAA and Forchlorfenuron (CPPU) can delay the maturation process and change the flow of phenylpropane metabolic pathways [23,24]. In addition, there is a lot of evidence from the transcriptome and metabolome that ABA can respond to environmental signals such as solar ultraviolet-B (UV-B) radiation [25], water deficit [26,27] and high temperature [28], and greatly affect the ripening and quality of grape fruits [29][30][31]. However, there is still a lack of accurate quantification of multiple phytohormones and investigation of the trends of phytohormone changes in grape berries.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, even when environmental conditions measured at bunch level and water stress were not as limiting as in 2017, SS vines showed a reduction in vegetative growth and an increase in berry phenolics and antioxidant capacity. This scenario was also observed in 2016, a climatological milder season, suggesting that plant vigour and metabolic activity in highaltitude viticulture can be affected by other environmental factors, such as UV-B radiation (Alonso et al, 2016), when water and temperature are not limiting. At the 2017 harvest, DS vines presented more TP with no differences in TA compared to SS vines.…”
Section: Discussionmentioning
confidence: 61%
“…High UV-B radiation level has been shown to increase secondary antioxidant metabolites in berry skins, also affecting vegetative growth and fruit yield (Berli et al, 2013;Berli et al, 2015). Moreover, high levels of UV-B, especially when combined with other abiotic stresses such as moderate water stress, may cause a more prominent reduction in chlorophyll photosynthetic pigments and an increase in the accumulation of berry skin polyphenols, although with a reduction in yield, implying more severe stress conditions than if exposed to single abiotic stressors (Berli et al, 2015;Alonso et al, 2016;Doupis et al, 2020). Among other stressful factors, air temperatures above 35 °C decrease the biosynthesis of secondary metabolites (Mori et al, 2007;Zarrouk et al, 2016), as well as photosynthesis rate and vegetative growth (Galat Giorgi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%